The application of the concept of best interests of the child in participating in the matrimonial proceeding in the Shariah court - Yaakob A.; Ahmad A.; Musa A.S.; Rajuddin A.S.; Zakaria M.Z.; Awal N.A.M.; Samuri M.A.A.; Mushaddad Hasbullah (American Scientific Publishers, 2024)
Indexed by SCOPUS